Perwujudan Ketidaksantunan Berbahasa Pada Komentar Pembaca Berita Pilpres 2014 Di Portal Berita Vivanews.Com Edisi Juni 2014 - Munawaroh, Aminatul, Dra. Atiqa Sabardila, M.Hum (2015)
Vivanews.com as of the property business supporter from contestant of president election 2014, news give much put contestant president. The matter fabricated comentaters reader in see page enough hard. Readers thing commentate news posting of President election 2014 with candidate of president this news. In fact little not comentate reader use words diry whit purpose to drop candidate of president 2014 in the news. The objective of this experiment is 1) to describe the shape of well manered speaking in the comentater news reader of president election 2014 in the news portal Vivanews.com June 2014 edition. 2) To describe the deviation principles of well manered speaking in the comentater news reader of president election 2014 in the news portal Vivanews.com June 2014 edition. The type of this experiment is a qualitative descriptive experiment. The source of data from this experiment is postings of Presiden election news in news portal Vivanews.com June 2014 edition. The data from this experiment is the language of the commentater news readers of Presiden election 2014 in news portal Vivanews.com June 2014 edition. The collection of data from this experiment is method using and listening and writing technique. The results of this experiment shows the act of well-manered speaking in the commentator news reader of Presiden election 2014 has categories of not very well-manered, not well-manered, and rather well-manered because in the readers discourse, there were lots of bad discourses, heartful ones, jokes and swearing. The Deviation principles of well-manered speaking in the commentator news reader of President election 2014 in portal news Vivanews.com has 5 maxim deviations. The 5 maxim are maxim achievement, maxim wisdom, maxim generosity, and maxim simplicity. The maxim achievement has 19 announcement of deviation, maxim wisdom has 14 announcement of deviation, maxim generosity has 13 announcement of deviation, maxim simplicity has 6 announcement of deviation and maxim deliberation has 4 announcement of deviation.